The deep roots of meritocracy - Bruni, Luigino (2022)
Meritocracy, whose teachings are the blaming of the poor and the ethical justification of inequality, is becoming the new religion of our age. Thanks to meritocracy, the natural inequality of the capitalist market, which is artificially mitigated in society by political and social means because it is considered morally and socially undesirable, has become a moral property. Academic merit leads to widely differing privileges and positions, which have sustained and continue to sustain the fabric and inequalities of our society. If we want to break the spiral of inequality and exclusion, we must put in place anti-meritocracy education policies, in the same way that during the twentieth century Europe was able to introduce free, universal and compulsory schooling.